Rolul stimei de sine în formarea imaginii de sine la adolescenți (Studia Doctoralia Psychology and Educational Science, 2013)
The main objective of this research consists in studying psychosocial aspects of the relationship that is established between the level of the quality of self image and self-esteem in adolescents. Self-esteem play an important role in the self image of teenagers and young people. Teenagers with a high level of self-esteem have clear and stable views about themselves, talk about them in a consistent, positive way. Teenagers with a low self-esteem have the feeling that they do not know too well each other and talk about them in a unreliable and ambiguous way. They are also pretty reserved in initiating social contacts.
Keywords: self-image; self esteem; the facets of self